The Values of Islamic Guidance and Counseling in Javanese Culture - Cholil, Cholil (Nursyam Center, 2024)
This research aims to determine the various values of Islamic guidance and counseling in Javanese culture, the implementation of Islamic guidance and counseling values in Javanese culture, and the relevance of Islamic guidance and counseling in Javanese culture. This is because a counselor cannot choose clients to carry out the counseling process. Each client has a different cultural background, one of which is Javanese culture. This study is qualitative research with a literature study approach with two types of data. Primary data was obtained through literature such as the Al-Qur'an, books on Islamic guidance and counseling, and Javanese culture. Secondary data was obtained through journals and information sources from the internet which contain values related to Islamic counseling guidance and Javanese culture. The results of this research are the values of Islamic guidance and counseling in Javanese culture, namely the belief in making choices through Islamic teachings and Javanese culture that have been passed down from generation to generation. Culture can influence the success of counseling because it can be seen in how clients are handled. The implementation of Islamic guidance and counseling in Javanese culture varies, for example, friendly greetings, greetings, and politeness.